2015
DOI: 10.4103/1735-3327.150289
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the nasopalatine canal with cone-beam computed tomography in an Iranian population

Abstract: Background:Implant placement plays a vital role in oral rehabilitation following loss of the incisors. Thus, having knowledge of anatomical variations of adjacent neurovascular structures especially the nasopalatine canal (NPC) is essential. Due to the lack of basic information in Iran about the morphology of this canal and the probability of its variety in different populations, this study was designed on an Iranian population.Materials and Methods:In this descriptive study, we selected cone-beam computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
28
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 8 publications
12
28
3
3
Order By: Relevance
“…The mean length of nasopalatine canal in the present study was higher than that reported by some earlier research by Nasseh et al On contrary, the nasopalatine canal length in the present study was similar to that reported in two studies by Kajan et al (2015); Salemi et al (2016). [3,12] In the present study, the length of nasopalatine canal was shorter in females than in males but it was not statistically significant. On the other hand, few researchers: Kajan et al (2015); Tozum et al (2012); Nasseh et al (2017) reported that the length of nasopalatine canal was 1,12,13 significantly higher in males than females.…”
Section: Discussioncontrasting
confidence: 69%
“…The mean length of nasopalatine canal in the present study was higher than that reported by some earlier research by Nasseh et al On contrary, the nasopalatine canal length in the present study was similar to that reported in two studies by Kajan et al (2015); Salemi et al (2016). [3,12] In the present study, the length of nasopalatine canal was shorter in females than in males but it was not statistically significant. On the other hand, few researchers: Kajan et al (2015); Tozum et al (2012); Nasseh et al (2017) reported that the length of nasopalatine canal was 1,12,13 significantly higher in males than females.…”
Section: Discussioncontrasting
confidence: 69%
“…For the canal length, the inclination related to the hard palate, and the incisive foramen anteroposterior diameter, no statistical signifi cance between genders was observed except for the canal height that was found shorter in females. Kajan et al 14 in their study on Iranian population found that mean values for oral and nasal opening of NPC were 3.53 ± 1.01 and 3.7 ± 2.3 mm respectively, whereas in the present study, it was 3.38 ± 1.52 and 3.40 ± 1.02 mm in males and 2.90 ± 1.42 and 2.98 ± 1.00 mm in females.…”
Section: Discussioncontrasting
confidence: 45%
“…For Al-Amery et al (3) and Kajan et al (7), the labiopalatal (anteroposterior) diameter of the IF was 2.80 ±0.82 and 3.53 ± 1.1 mm respectively.…”
Section: Discussionmentioning
confidence: 91%